A novel activation pathway for mature thymocytes. Costimulation of CD2 (T,p50) and CD28 (T,p44) induces autocrine interleukin 2/interleukin 2 receptor-mediated cell proliferation (The Rockefeller University Press, 1988)
Prior studies have shown that thymocytes, unlike peripheral T cells, do not proliferate in response to mitogenic combinations of anti-CD2 mAbs. The present study demonstrated that stimulation by a mitogenic anti-CD2 combination (9-1 plus 9.6) with anti-CD28 induced vigorous thymocyte proliferation in the absence of exogenous IL-2. This thymocyte proliferation was IL-2 dependent as shown by the complete inhibition using anti-IL-2-R mAbs. Induction of IL-2-R transcripts was detected in thymocytes stimulated by the anti-CD2 antibody combination alone or the anti-CD2 combination plus anti-CD28 antibody. However, induction of IL- 2 transcripts was observed only in thymocytes triggered jointly by the anti-CD2 combination plus anti-CD28 antibodies. The double-negative (CD4-8-) or CD1+ thymocytes isolated by sorting or by panning were unresponsive to CD2/CD28 triggering. The same mitogenic signal could induce vigorous proliferation of thymocytes with a mature phenotype, i.e., CD3+CD4+ or CD3+CD8+ thymocytes. Immunofluorescence studies demonstrated that the majority of CD3+ thymocytes were CD28+, and most of the CD28+ cells were located in the medullary compartment of thymus. These results indicated that the T cell lineage surface molecules CD28 and CD2 are involved in the regulation of expansion and further differentiation of mature thymocytes.